Dual production of polyhydroxyalkanoates and antibacterial/antiviral gold nanoparticles - Paxinou, Alexandra; Marcello, Elena; Vecchiato, Vittoria; Erman, Lara; Wright, Edward; Noble, Brendon; McCormick, Adele; Basnett, Pooja (Frontiers in Nanotechnology, 2023)
Gold nanoparticles (AuNPs) have been explored for their use in medicine. Here, we report a sustainable, and cost-effective method to produce AuNPs using a bacterial strain such as Pseudomonas mendocina CH50 which is also known to be a polyhydroxyalkanoate (PHA) producer. A cell-free bacterial supernatant, which is typically discarded after PHA extraction, was used to produce spherical AuNPs of 3.5 ± 1.5 nm in size as determined by Transmission Electron Microscopy (TEM) analysis. The AuNPs/PHA composite coating demonstrated antibacterial activity against S. aureus 6538P, and antiviral activity, with a 75% reduction in viral infectivity against SARS-CoV-2 pseudotypedvirus.